The Development of Interim Measures Procedure in Cases Against Poland Before CJEU - Cieśliński Aleksander (Wroclaw Review of Law, Administration and Economics)
This article presents a contemporary model of applying interim measures by the Court of Justice of the European Union, drawing on an increasingly rich body of case law in Polish cases. The disputes that the European Commission has engaged in with the Polish government, along with the non-standard obstruction in compliance with EU law, have become the basis for a new approach to this ancillary procedure offered by the Rules of Procedure of the Court. The article focuses on two sensitive areas where judicial intervention has proved necessary, the protection of the natural environment and ensuring the rule of law, especially in the operation of the national judiciary. There is no doubt that this body of work constitutes a significant contribution to the overall development of EU law, as it has led to the adoption of a completely new interpretation of Article 279 TFEU. According to the latest case law, the possibility of imposing financial penalties on member states is not limited to cases provided for in Article 260 TFEU, that is, non-compliance with a judgment finding a breach of EU law; these penalties can also be imposed in cases of non-compliance with the Court’s interim orders.